2021
DOI: 10.1002/col.22711
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a color tolerance for yarn‐dyed fabrics from different color‐depth yarns

Abstract: Yarn-dyed fabric is often woven from warp and weft yarns in the same color depth to ensure a uniform color appearance. The difference in color depth between warp and weft tends to result in the uneven color of the yarn-dyed fabric. This article aims to establish a color tolerance for yarn-dyed fabric that can be woven with a qualified color appearance but from the warp and weft yarns in different color depths. A total of 27 yarn-dyed fabric samples in three color series (red, yellow, and blue) were evaluated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Based on the colorimetric parameters above, this study adopted the CIEDE 2000 and CMC formulae defined by the Color Measurement Committee of the Society of Dyers and Colorists for the optimum values of color difference. The weighing factors were set as follows: kL = 1.5, kC = 1.9, and CMC = 2:1 [31,32]. The values were converted through the ColoCalculator programs, which are provided by Lindbloom and Osram Inc. (MA, USA).…”
Section: Characterization and Chromatic Analysesmentioning
confidence: 99%
“…Based on the colorimetric parameters above, this study adopted the CIEDE 2000 and CMC formulae defined by the Color Measurement Committee of the Society of Dyers and Colorists for the optimum values of color difference. The weighing factors were set as follows: kL = 1.5, kC = 1.9, and CMC = 2:1 [31,32]. The values were converted through the ColoCalculator programs, which are provided by Lindbloom and Osram Inc. (MA, USA).…”
Section: Characterization and Chromatic Analysesmentioning
confidence: 99%
“…This method requires human participation and is at a low level of automation. Jiang 16 used the auto-correlation function (ACF) to extract the repeat unit of fabric patterns after grayscale and regularization processing. This method based on the auto-correlation curve is easily affected by other factors like image skew, resulting in unstable extraction results.…”
Section: Fabric Image Pre-processingmentioning
confidence: 99%
“…Therefore, it is required that the warp and weft yarns should have no apparent color difference if the yarn-dyed fabric is woven into a uniform color appearance (Karst et al, 2004;Shen et al, 2016). It was recently reported that, at the time of the transformation from the colored yarns to the yarn-dyed fabric, changes in lightness and chroma were observed for the effects of light traps and gloss, but hue angles remained constant (Moussa et al, 2009, 2008, Wang et al, 2022. Based on this finding, it was proposed that yarn-dyed fabric could be woven from warp and weft yarns in different color depths to meet the requirement on a uniform color appearance.…”
Section: Introductionmentioning
confidence: 99%